Comparison of Gafchromic EBT2 and EBT3 for patient‐specific quality assurance: Cranial stereotactic radiosurgery using volumetric modulated arc therapy with multiple noncoplanar arcs. Issue 8 (26th July 2013) - Fiandra, Christian; Fusella, Marco; Giglioli, Francesca Romana; Filippi, Andrea Riccardo; Mantovani, Cristina; Ricardi, Umberto; Ragona, Riccardo
Abstract : Purpose: : Patient‐specific quality assurance in volumetric modulated arc therapy (VMAT) brain stereotactic radiosurgery raises specific issues on dosimetric procedures, mainly represented by the small radiation fields associated with the lack of lateral electronic equilibrium, the need of small detectors and the high dose delivered (up to 30 Gy). Gafchromic TM EBT2 and EBT3 films may be considered the dosimeter of choice, and the authors here provide some additional data about uniformity correction for this new generation of radiochromic films. Methods: : A new analysis method using blue channel for marker dye correction was proposed for uniformity correction both for EBT2 and EBT3 films. Symmetry, flatness, and field‐width of a reference field were analyzed to provide an evaluation in a high‐spatial resolution of the film uniformity for EBT3. Absolute doses were compared with thermoluminescent dosimeters (TLD) as baseline. VMAT plans with multiple noncoplanar arcs were generated with a treatment planning system on a selected pool of eleven patients with cranial lesions and then recalculated on a water‐equivalent plastic phantom by Monte Carlo algorithm for patient‐specific QA. 2D quantitative dose comparison parameters were calculated, for the computed and measured dose distributions, and tested for statistically significant differences. Results: : Sensitometric curves showed a different behavior above dose of 5 Gy for EBT2 and EBT3 films; with the use of inhouse marker‐dye correction method, the authors obtained values of 2.5% for flatness, 1.5% of symmetry, and a field width of 4.8 cm for a 5 × 5 cm 2 reference field. Compared with TLD and selecting a 5% dose tolerance, the percentage of points with ICRU index below 1 was 100% for EBT2 and 83% for EBT3. Patients analysis revealed statistically significant differences ( p < 0.05) between EBT2 and EBT3 in the percentage of points with gamma values <1 ( p = 0.009 and p = 0.016); the percent difference as well as the mean difference between calculated and measured isodoses (20% and 80%) were found not to be significant ( p = 0.074, p = 0.185, and p = 0.57). Conclusions: : Excellent performances in terms of dose homogeneity were obtained using a new blue channel method for marker‐dye correction on both EBT2 and EBT3 Gafchromic TM films. In comparison with TLD, the passing rates for the EBT2 film were higher than for EBT3; a good agreement with estimated data by Monte Carlo algorithm was found for both films, with some statistically significant differences again in favor of EBT2. These results suggest that the use of Gafchromic TM EBT2 and EBT3 films is appropriate for dose verification measurements in VMAT stereotactic radiosurgery; taking into account the uncertainty associated with Gafchromic film dosimetry, the use of adequate action levels is strongly advised, in particular, for EBT3.